The New Face of Technology-Enhanced Language Learning (TELL) with Artificial Intelligence (AI): Teacher perspectives, practices, and challenges - Novawan, Adriadi; Walker, Stuart Anthony; Ikeda, Osamu (Politeknik Negeri Jember, 2024)
The field of language education has recognized educational transformations driven by advancements in information and communication technology (ICT). From traditional tools to intelligent digital innovations, the journey has been marked by continuous evolution. The integration of Artificial Intelligence (AI) in language education, termed Intelligent Technology-Enhanced Language Learning (ITELL), represents a paradigm shift. This paper explores the reality of ITELL in higher education, focusing on how AI is used in language teaching, teachers' perspectives, policy implications, challenges, and strategies employed. A qualitative case study approach explored the integration of AI in TELL in higher education. Seven English language teachers in Indonesia, employing AI tools, participated in in-depth, semi-structured interviews. Thematic analysis of interview data provides insights into teachers' practices, perceptions, and challenges of AI in language education. Methodological rigour was ensured through member-checking, peer debriefing, and adherence to ethical guidelines. The findings emphasize the positive impact of AI on enriching teachers' perspectives, enhancing materials development, enlivening in-class teaching, and facilitating efficient assessments. However, challenges such as depersonalization and ethical considerations were highlighted. A hybrid model that balances AI-driven personalization with human interaction was promoted. Fundamental prerequisites for successful AI integration include teacher professional development, aligned curriculum, pedagogical exploration, and a comprehensive policy framework.